Classification of geological materials on geochemical lithogenes: Illustration on a case study in Gejiu area of Yunnan Province, China. (November 2022) - Wu, Yuan; Gong, Qingjie; Liu, Ningqiang; Wu, Xuan; Yan, Taotao; Xu, Shengchao; Li, Wangju
Abstract: Geochemical gene, especially the lithogene, is a new promising concept proposed recently in discrimination and traceability of geological materials. The theory and application of the LG01 and LG03 lithogenes are introduced firstly. In order to test their properties and applications, four types of geological materials such as samples from a granite intrusion to its weathered products, some altered granites, some fresh rocks with different lithology, and stream sediments from regional geochemical survey in Gejiu area of Yunnan province, China are selected as a case illustration. The LG01 and LG03 lithogenes keep steady during weathering and alteration processes which consolidates the idea that geochemical lithogene and can be viewed as a tool to classify geological materials compositionally. Based on the classification results of LG01 and LG03 lithogenes, an integrated classification result of lithogenes, LG_CR, is proposed. The results on collected samples in Gejiu area indicate that the LG_CR can be used not only to classify geological materials such as fresh rocks, altered rocks, soils, and stream sediments compositionally but also to trace their sources or provenances as well. Furthermore, the compositional classification of LG_CR on geochemical lithogenes are basically consistent with the results derived on petrologic study which may be helpful to petrologic mapping in coverage areas of bedrocks. Highlights: Application of geochemical lithogenes are illustrated on weathered and altered products. An integrated classification result of lithogenes, LG_CR, is proposed. LG_CR is a tool to classify and trace geological materials compositionally.